O uso da experimentação como instrumento de ensino de física na formação continuada de professores - Araújo, Alessandro Batista de (2015)
This work concerns about to understand the relationship between experimental practices and everyday life in various scholar comunities relateds to knowledge construction and scientific language concepts, mainly in Physics language, based on answers to a questionnaire by high school Physics teachers. The investigation was based on the existence of challenges and difficulties with scientific language, particularly in physics, by the students and the infrequently and applicability of experiments in schools, noting answers on what are the times when educators use certain experiments and reasons why they choose to perform them. We intend to establish a relation between experimental practice and the school universe and which are the concepts of teachers, who answered the questionnaire, about how this process interfere in the knowledge construction in the teaching of Sciences, especially in Physics. By the dialog about differents possibilities of understand the relation between the theory and the experiment, we propose, based on the ideas of Thomas Kuhn, a reflection about how are chosen the methods to perform the experimental practice, as well as the standard used and the new ways to verify phenomena as a teaching tool. These ideas allow to analize if and how the traditional scientific method influences teachers on their decisions about the experimental practice and on the observation of phenomena, associated with the challenges of acceptance or refutation of the new knowledges or of the new concepts that somehow are related with the paradigm shift of Kuhn.